2015
DOI: 10.2337/dc14-2073
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Risk of Type 2 Diabetes: A Meta-analysis of Prospective Studies

Abstract: OBJECTIVEIt remains unclear how many hours of sleep are associated with the lowest risk of type 2 diabetes. This meta-analysis was performed to assess the dose-response relationship between sleep duration and risk of type 2 diabetes. RESEARCH DESIGN AND METHODSPubMed and Embase were searched up to 20 March 2014 for prospective observational studies that assessed the relationship of sleep duration and risk of type 2 diabetes. Both semiparametric and parametric methods were used. RESULTSTen articles with 11 repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
479
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 680 publications
(535 citation statements)
references
References 54 publications
(80 reference statements)
22
479
2
12
Order By: Relevance
“…Our metaanalysis takes the evidence further by including 18 studies and analyzing the association of different categories of short sleep (,5, 5-6, and 6-7 h) duration as well as long sleep (8-9 and .9 h) with MetS. In fact, results of our metaregression sensitivity analysis show that exclusion of the data for greater than 9 hours of sleep duration from the rest of the different durations of sleep (,5, 5-6, 6-7, 8-9), predicts a dose-dependent response, a finding not shown in prior metaanalyses (19,20,46). In other words, every 1 hour decrease in sleep duration corresponds to a 0.06 increase in the OR of having MetS.…”
Section: Systematic Reviewsupporting
confidence: 55%
“…Our metaanalysis takes the evidence further by including 18 studies and analyzing the association of different categories of short sleep (,5, 5-6, and 6-7 h) duration as well as long sleep (8-9 and .9 h) with MetS. In fact, results of our metaregression sensitivity analysis show that exclusion of the data for greater than 9 hours of sleep duration from the rest of the different durations of sleep (,5, 5-6, 6-7, 8-9), predicts a dose-dependent response, a finding not shown in prior metaanalyses (19,20,46). In other words, every 1 hour decrease in sleep duration corresponds to a 0.06 increase in the OR of having MetS.…”
Section: Systematic Reviewsupporting
confidence: 55%
“…A Finnish study in overweight individuals with impaired glucose tolerance found an increased risk of T2DM only in participants with long sleep duration ⩾9 h (hazard ratio (HR) 2·29, 95 % CI 1·38, 3·80) (14) . Finally, two recent meta-analyses of nine (17) and fourteen (18) prospective cohort studies have also confirmed the U-shaped relationship (Fig. 1).…”
Section: Association Between Sleep Duration and The Risk Of Type 2 DIsupporting
confidence: 54%
“…Meta-analyses support a U-shaped association between sleep duration and incident type 2 diabetes [8,9]. Furthermore, sleep duration predicts cardiovascular outcomes [10], and both short [11][12][13][14] and long [14,15] sleep time is associated with incident CHD in prospective studies.…”
Section: Introductionmentioning
confidence: 92%